2011
DOI: 10.3109/08982104.2011.573793
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thermal-oxidative stability and antiglioma activity of Zanthoxylum tingoassuiba essential oil entrapped into multi- and unilamellar liposomes

Abstract: Zanthoxylum tinguassuiba essential oil (ZtEO) contains α-bisabolol, a known antiglioma sesquiterpene, among other potentially active substances. Medical applications of this essential oil require advances in the design of distinctive carriers due to its low water solubility and easy degradation by heat, light, and oxygen. The aim of this work was to evaluate enhancement in oxidative stability and the ability to reduce glioblastoma cell viability of ZtEO loaded into liposomes. Multi- and unilamellar vesicles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 24 publications
4
25
0
Order By: Relevance
“…All loaded lipid vesicles showed narrow size distribution (PDI < 0.21), proving a good homogeneity and a low tendency of aggregation. The incorporation of SE extract improved the homogeneity, while the empty vesicles had a wider size distribution than SE-loaded vesicles in agreement with literature data [44,45]. The zeta potential values were in the range of −43 ± 1.03 mV ÷ −37 ± 0.23 mV being in accordance with the literature data, all samples indicated moderate stability [46].…”
Section: Characterization Of Se Extract−loaded Lipid Vesiclessupporting
confidence: 90%
“…All loaded lipid vesicles showed narrow size distribution (PDI < 0.21), proving a good homogeneity and a low tendency of aggregation. The incorporation of SE extract improved the homogeneity, while the empty vesicles had a wider size distribution than SE-loaded vesicles in agreement with literature data [44,45]. The zeta potential values were in the range of −43 ± 1.03 mV ÷ −37 ± 0.23 mV being in accordance with the literature data, all samples indicated moderate stability [46].…”
Section: Characterization Of Se Extract−loaded Lipid Vesiclessupporting
confidence: 90%
“…Exploration of natural plant products as an option to find new chemicals as anticancer agents is one of the fastest growing areas of research, and the available studies indicate EOs from various plant species and their constituents as anticancer agents [63]. A recent study has shown that EOs can be a potential alternative for glioblastoma treatment [64][65][66]. Quassinti et al [65] showed that EO of Hypericum hircinum had antiproliferative activity on human glioblastoma tumor cells T98G.…”
Section: Discussionmentioning
confidence: 99%
“…Quassinti et al [65] showed that EO of Hypericum hircinum had antiproliferative activity on human glioblastoma tumor cells T98G. Detoni et al [64] demonstrated that EO of Zanthoxylum tinguassuiba could be a potential alternative for gliobastoma treatment. As reported by Bayala et al [66], essential oil of Ageratum conyzoides shows the highest antitumor activity on SF-763 cells, while the SF-767 glioblastoma cell line was the most sensitive to EOs of Ocimum basilicum and Lippia multiflora.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the phenyl propenes; estragole and isoeugenol, and the monoterpenes; eucalyptol, pulegone, terpineol, and thymol were chosen as models of essential oil components. These components exhibit considerable biological effects including antimicrobial, antifungal, antinociceptive, anti-inflammatory (Dogan et al 2017;Kfoury et al 2016;de Sousa et al 2011;Melo Júnior et al 2017;de Oliveira et al 2012;Wattanasatcha, Rengpipat, and Wanichwecharungruang 2012;Riella et al 2012) antioxidant (Kfoury et al 2014), and anesthetic (Reiner, Perillo, and García 2013) activities.…”
Section: Introductionmentioning
confidence: 99%